Bayesian Credible Sets for Odds Ratio of Two Binomial Proportions Using Double Sampling with False-Positive Misclassification - Rahardja, Dewi (American journal of mathematical and management sciences, 2016)
A Bayesian approach is considered for a point and interval estimation for odds ratios of two binomial proportion parameters using double-sampling data subject to false-positive misclassification. For such data, we derive an easy-to-implement, closed-form algorithm for drawing from the posterior distributions. Application of this algorithm is illustrated using data collected about student laboratory grades from a course.